Ypthima kedarnathensis</> Singh - New Synonym of Ypthima sakra Moore (Nymphalidae: Satyrinae) from Garhwal Himalaya, India - Sharma, Narender (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.